Tinjauan Yuridis Normatif Terhadap Peraturan BWI tentang Keharusan Izin Persetujuan Ahli Waris Wakif dalam Perubahan Nadzir Maupun Peruntukan Wakaf - Shohiba Mazaya Mubaroka (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the legal implications of regulations issued by the Indonesian Waqf Board (BWI) regarding the necessity of obtaining approval from the heirs of the waqif (donor) for changes in nazhir (waqf administrators) or waqf purposes when the waqif has passed away. It examines the alignment of these regulations with both positive law and Islamic law principles, highlighting potential challenges and contradictions. The study emphasizes the significance of ensuring effective waqf management while maintaining compliance with Islamic law's foundational principles, which assert that waqf assets are separated from personal ownership and cannot be sold, rented, or inherited. However, current BWI regulations require heirs' involvement, raising questions about their potential impact on the flexibility and independence of waqf governance. The research concludes that while involving heirs aims to safeguard waqf assets, it may also introduce unnecessary complexities, potentially hindering the optimal use of waqf resources for public benefit.